Universitas Negeri Jakarta’s Strategy for Enhancing Professionalism and Competitive Advantage Towards Becoming a World Class University (WCU) - Budianto; Kasful Anwar Us; Fridiyanto (Future Tecno-Science Publisher, 2025)
This study aims to examine the strategic efforts undertaken by Universitas Negeri Jakarta (UNJ) to enhance human resource professionalism and build competitive advantage in its pursuit of becoming a World Class University (WCU). The era of globalization demands higher education institutions to continuously innovate and improve their quality to remain competitive at the international level. This research employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with UNJ leadership, document analysis of UNJ’s strategic plan, and indirect observation. The findings reveal that UNJ has implemented various strategies, including faculty and staff qualification improvement programs through advanced studies and professional training, curriculum development aligned with Industry 4.0, enhancement of international scientific publications, and expansion of global partnership networks. However, the university still faces several challenges, such as limited funding for large-scale research and the need for a more globally oriented academic culture. The study recommends strengthening multinational research collaboration, increasing financial support for research-active faculty members, and accelerating institutional digital transformation to support UNJ’s vision of becoming a World Class University.